Plasma Exosomes Spread and Cluster Around β-Amyloid Plaques in an Animal Model of Alzheimer’s Disease - Zheng, Tingting; Pu, Jiali; Chen, Yanxing; Mao, Yanfang; Guo, Zhangyu; Pan, Hongyu; Zhang, Ling; Zhang, Heng; Sun, Binggui; Zhang, Baorong (Frontiers in Aging Neuroscience, 2017)
Exosomes, a type of extracellular vesicle, have been shown to be involved in many disorders, including Alzheimer’s disease. Exosomes may contribute to the spread of misfolded proteins such as amyloid -β and α-synuclein. However, the specific diffusion process of exosomes and their final destination in brain are still unclear. In the present study, we isolated exosomes from peripheral plasma and injected them into the hippocampus of an Alzheimer’s disease mouse model, and investigated exosome diffusion. We found that injected exosomes can spread from the dentate gyrus to other regions of hippocampus and to the cortex. Exosomes targeted microglia preferentially; this phenomenon is stable and is not affected by age. In Alzheimer’s disease mice, microglia take up lower levels of exosomes. More interestingly, plasma exosomes cluster around the amyloid-β plaques and are engulfed by activated microglia nearby. Our data indicate that exosomes can diffuse throughout the brain and may play a role in the dynamics of amyloid deposition in Alzheimer’s disease through microglia.